Diskursus Akuntansi Zakat: Evaluasi Praktis Laporan Keuangan Lazisnu Kabupaten Kudus - Baihaqi, Jadzil (AKTSAR: Jurnal Akuntansi Syariah, 2018)
This research aims to identify and explain application about the implementation of PSAK 109 Zakat Accounting to financial reports of Zakat Management. The method used is a case study of LAZISNU Kudus by analyzing the 2017 financial statements and by interviewing the manager. This study finds that, in general, financial reports of LAZISNU Kudus are not in accordance with PSAK 109 because there are two incompatibilities. First, there are only two elements of the five elements in the financial statements, that are the Statement of Changes in Fund and the Statement of Cash Flow. Secondly, Amil funds are not properly recognized and presented, because they were not separated from zakat funds and infaq/shadaqah funds.